Sensors in the age of the internet of things : technologies and applications - Postolache, Octavian Adrian; Sazonov, Edward; Mukhopadhyay, Subhas Chandra (IET control, robotics and sensors series ;, 2019)
The following topics are dealt with: Internet of Things; wireless sensor networks; data analysis; logistics; sea ports; production engineering computing; signalling protocols; radio networks; local area networks; telecommunication congestion control.